Pengaruh Paparan Konten Edukasi Karier di Media Sosial TikTok terhadap Kesiapan Perencanaan Karier Generasi Zelenial di Universitas Bengkulu - Irawan, Dimas Agus; Afrilia, Sahara; Saputra, Fajri; Nopriyanti, Fickah; Yasinta, Desvi; Hidayat, Zhafif (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study was conducted to analyze the influence of career education content on TikTok social media on the career planning readiness of Generation Z at the University of Bengkulu. This study used career planning content as the Y variable and educational content as the X variable, a widely used test variable. However, in the context of similar research, researchers have limited the research object to only one object of study. The approach used in this study is a quantitative method, a method rarely used in similar research contexts. The use of Generation Z students certainly offers a new perspective, considering that this generation grew up with internet technology and does not need to adapt to digital developments. This study used a quantitative approach, with data obtained through primary data distributed to respondents using a non-probability sampling technique. The data were analyzed using simple linear regression analysis to examine the influence of the test variables, with a significance level of α = 0.005 (5%). This study uses a Probit Regression model as an alternative to modeling the dependent variable, focusing on the Y variable, which has a value of 0 or 1, thus assuming that Y follows a standard normal distribution. This study shows that exposure to career education content on TikTok is accepted and has a positive effect on the career planning of Generation Z at the University of Bengkulu. This study is limited by its population coverage. The researcher did not have a complete list of all active TikTok users within Generation Z at the University of Bengkulu, represented by 110 respondents from the original user base. Therefore, the population was expanded to an infinite size. This study provides implications for whether career education content on TikTok is effective in developing career plans and preparing for the world of work.